USING AUTHENTIC MATERIALS IN ESP CLASSROOMS: BENEFITS AND LIMITATIONS - Norboboeva Saida Azamatovna (Bright Mind Publishing, 2025)
This article explores the role of authentic materials in English for Specific Purposes (ESP) instruction, focusing on their benefits and potential drawbacks. Authentic materials—such as medical case notes, technical manuals, or business emails—expose learners to real-world language use relevant to their professional goals. Research shows that authentic materials enhance learner motivation, improve contextual understanding, and foster critical thinking. However, challenges include difficulty in adapting complex materials to the learners’ language level and lack of teacher training. The article concludes that, when carefully selected and scaffolded, authentic materials are a powerful tool in ESP classrooms.
Keywords: Authentic materials, ESP, professional English, real-world context, language learning.